10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Hereditary neuropathy with liability to pressure palsies (HNPP) is an autosomal dominant disorder caused by a PMP22 gene deletion (or mutations), characterized by recurrent, compression-induced mononeuropathies. Postpartum neurological complications are relatively common, but HNPP is rarely considered in their differential diagnosis. We report a case of a 38-year-old woman who developed acute painless bilateral lower limb paralysis following vaginal delivery complicated by prolonged lithotomy positioning and vacuum extraction. Electroneuromyography revealed a demyelinating sensorimotor polyneuropathy with conduction block at the fibular neck, and genetic testing confirmed HNPP. This case underscores the importance of recognizing HNPP as a cause of postpartum paralysis, particularly in patients with a family history of recurrent nerve palsies. Multidisciplinary management, including genetic counseling and tailored obstetric planning for future pregnancies, is essential to optimize outcomes.